2018
DOI: 10.1002/chem.201704487
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐Driven Charge‐Transfer Organogels Built from Synergetic Hydrogen Bonding and Pyrene–Naphthalenediimide Donor–Acceptor Interactions

Abstract: The peptide-driven formation of charge transfer (CT) supramolecular gels featuring both directional hydrogen-bonding and donor-acceptor (D-A) complexation is reported. Our design consists of the coassembly of two dipeptide-chromophore conjugates, namely diphenylalanine (FF) dipeptide conveniently functionalized at the N-terminus with either a pyrene (Py-1, donor) or naphthalene diimide (NDI-1, acceptor). UV/Vis spectroscopy confirmed the formation of CT complexes. FTIR and H NMR spectroscopy studies underlined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Combination of donor and acceptor chromophore dyes in one molecule results in intramolecular charge transfer, which decreases the HOMO–LUMO band gap and shifts the absorption and emission maxima to higher wavelengths . Bartocci et al reported supramolecular gels from functionalized naphthalene bisimide and pyrene system using donor–acceptor interactions and charge transfer between the two moieties. Solar cell acceptors based on perylene bisimide coupled with pyrene demonstrated promising power conversion efficiency, which was due to the broad absorption and π‐electron delocalization leading to effective charge transport , .…”
Section: Introductionmentioning
confidence: 99%
“…Combination of donor and acceptor chromophore dyes in one molecule results in intramolecular charge transfer, which decreases the HOMO–LUMO band gap and shifts the absorption and emission maxima to higher wavelengths . Bartocci et al reported supramolecular gels from functionalized naphthalene bisimide and pyrene system using donor–acceptor interactions and charge transfer between the two moieties. Solar cell acceptors based on perylene bisimide coupled with pyrene demonstrated promising power conversion efficiency, which was due to the broad absorption and π‐electron delocalization leading to effective charge transport , .…”
Section: Introductionmentioning
confidence: 99%
“…Such a narrow space of 3.47 Å between NDI/pyrene and NDI/NDI leads to strong π⋅⋅⋅π interactions between these aromatic units, thus offering highly effective charge transfer interactions [27, 28] . As a result, we observed the original light‐yellow color of Ca‐NDI crystal become red for Py@Ca‐NDI crystal (Figure S8), indicating the occurrence of charge transfer interaction between NDI and pyrene [29] . Moreover, this highly ordered structure also results in the extensive electron delocalization and communication within such a host–guest MOF skeleton, which is supported by red‐shift absorption [27, 28] .…”
Section: Figurementioning
confidence: 88%
“…Hydrogen bonds, the interactions that occur between hydrogen atoms and a great number of electronegative atoms in biomolecules, play important roles in the formation of biological nanomaterials [49,50,51]. In the process of biomolecular self-assembly, the hydrogen bonds can promote the growth of biomolecules in one direction with a long-range order to form one-dimensional (1D) nanostructures.…”
Section: Internal Interactions Towards Biomolecular Self-assemblymentioning
confidence: 99%